ARTIFICIAL INTELLIGENCE IN TV CONTENT AUDIO DESCRIPTION - Ćitić, Tatjana T (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2026)
Abstract: Providers of audio-visual media services, especially media public services, are obliged to provide the accesibility of TV contents to the blind and visually impaired. Legal regulations differ from one country to another, but at the core of all legal acts, in case there is no obligatory quota, there is the tendency to make as many TV materials as possible accessible to the persons with impaired sight. At the age of expanded programme offer through linear broadcast of basic and specialised TV channels, along with video streaming platforms and non-linear services, particularly of “videos on demand“ (VoD), the development and implementation of artificial intelligence are recognised as the tool that could provide, with the implicit quality, a wider contents accessibility. Media experts, just like the users, recognise the advantages, but also the shortcomings in practical usage, the concept that will be presented in this paper through scientific interviews conducted with the experts for the access services from European public service media, such as the BBC and TV France, and with a blind person, a specialised consultant within the team of the Radio-Television of Serbia for creating scenarios for audio-description. The aim of this paper is to use a case study, scientific interviews and analysis of technical-technological possibilities, current initiatives in the development of services for availability and new programme activities, to observe the benefits, as well as to point at the drawbacks in the current degree of implementing artificial intelligence and in the advantages of the presence of human factor in the process of adjusting the programmes for the blind and visually-impaired.